Etika Bertetangga Dalam Presfektif Hadis - Abdul Pandi; Arifuddin Ahmad; Erwin Hafid (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
Researchers are interested in researching this in order to find out: Neighboring ethics in a hadith perspective. Aims to find out about: neighborly ethics, neighborly ethics in the hadith perspective and the virtues of neighbors. This research is entirely in the nature of library research. The results of this study indicate that, neighborly ethics in Islam is part of the guidelines and ethics in neighbors that need to be considered by Muslims in all lines. Neighbors are people around us who need to be respected and treated in the best possible way because every day we interact with people around us. Therefore, we need to apply neighborly ethics in accordance with Islamic teachings so that relations with neighbors remain harmonious. and established good friendships. Neighboring ethics among Muslims, This treatment is not only given to our neighbors whose background is Muslim, but also to our neighbors who are non-Muslims. In fact, in order to protect the rights and honor of his neighbours, Al-Hasan has no problem giving sacrificial meat to non-Muslim neighbours, both Jews and Christians. The virtue of having a ladder because neighbors are the closest family from the existing environment, and live side by side with each other. If every neighbor respects other neighbors, and everyone glorifies their neighbors, the community will undoubtedly be good, because a sense of brotherhood has been created, mutual love, and mutual respect for other neighbors. Humans do not only establish a vertical relationship with Allah (read: hablul minallah) but also build an intimate horizontal relationship with other creatures, with the principle of mutual need.